Factors affecting recruitment and participation of bereaved parents and siblings in grief research. (April 2014) - Akard, Terrah Foster; Gilmer, Mary Jo; Miller, Katy; Steele, Amii Corbisiero; Hancock, Kelly; Barrera, Maru; Compas, Bruce; Davies, Betty; Dietrich, Mary S.; Fairclough, Diane L.; Hogan, Nancy S.; Vannatta, Kathryn; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> This study examined participation factors in a study of families (N = 84) within 1 year of a child's cancer-related death. Specific aims were to examine associations between: (a) recruitment variables (number of phone calls made to eligible families, number of calls answered by eligible families) and participation rates (study agreement and refusal) and (b) characteristics of deceased children (gender, age, length of illness, time since death) and participation rates. Characteristics of deceased children did not differ between participating and non-participating families. Researchers made significantly fewer calls to participating versus refusing families. Participating families most often agreed during the first successful call connection, and more calls did not mean more recruitment success. Thus, it is reasonable to limit the number of calls made to bereaved families. Despite recruitment challenges, many bereaved parents and siblings are willing and interested to participate in grief research.